Natural Spawning Breeding Techniques Analysis of Carp (Cyprinus carpio) in the Fish Seed Center (BBI) Bolangan, Tabanan, Bali - Kusmiatun, Anik; Arsana, I Made Putra; Istiqomah, Indah (Journal of Aquaculture and Fish Health, 2024)
Carp (Cyprinus carpio) is a freshwater fish species with a high tolerance to various environmental conditions. The present study aimed to analyze the seeding process of carp using a natural spawning method at the Fish Seed Center (BBI) Bolangan, Tabanan, Bali. The descriptive analysis had been used to analyze of the data collected through active participation, observation, and interviews. The carp natural spawning techniques at BBI Bolangan were conducted in an earthen pond. The breeding techniques include pond preparation, brood stock selections, fish spawning, larvae or seed maintenance, water quality control, disease control, and fish harvesting. Male and female parents in a 2:1 ratio were required for effective breeding. This natural hatching system produced up to 100806 eggs with a hatching rate of 74.4%, yielding 75000 larvae per female parent. After a week of care, the larvae have a 30% survival rate and are ready for cultivation in the following section (nursery II). We conclude that the Carp (Cyprinus carpio) breeding techniques at the Fish Seed Center (BBI) Bolangan, Tabanan, Bali are technically sound and feasible to apply.